SISTEM INFORMASI PEMESANAN TAKSI MOTOR DI CHUBA TRANS - , HENDRIANTO WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chuba Trans Motorcycle Taxi Reservation Information System was needed to assist and simplify the process of reservation record and reports preparation. The reservation still done by manually and the reports was made by a lot of paper, which is caused the reservation record and report preparations can not run fungsionally, effective, efficience and on time Chuba Trans Motorcycle Taxi Reservation Information System was built by using Visual Studio 2012 and MySQL database. This system information is used for processing data, such as operator data, armada data, customer data, driver data, driver status data, rental rates data, reservation data, deposit data, maintenance data and other expenditure data Chuba Trans Motorcycle Taxi Reservation Information System is a system that can be used to provide output in making reports of reservation report, deposit report, maintenance report and other expenditure report. The report data can be presented in daily, monthly, yearly and can be viewed as tables.